Chicken infectious anaemia, an immunosuppressive disease of poultry birds. Issue 4 (13th November 2014) - UMAR, S.; ULLAH, S.; YAQOOB, M.; SHAH, M.A.A.; DUCATEZ, M.
<x content-type="archive" xml:space="preserve">Abstract</x> Immunosuppressive viral diseases have become a major cause of mortality and economic losses in poultry industry mainly because of increased susceptibility of second bacterial infections and low response to vaccination. Nowadays chicken infectious anaemia is a great threat to poultry industry due to the large number of deaths and immuno-suppression it causes. Chicken anaemia virus replicates in erythroid and lymphoid progenitor cells, causing an apparent, sub-clinical infection that leads to depletion of these cells with consequent immunosuppressive effects. This review will summarise the currently available information about the chicken infectious anaemia virus and subsequent disease. Secondly, it will address the possible immune-pathogenic and immune-suppressive effects of chicken infectious anaemia in birds, including commercial poultry. Finally, the future prospects of vaccination against chicken infectious anaemia and other possible novel methods for the control of chicken anaemia virus are discussed.